1977
DOI: 10.1172/jci108845
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Thyroid Hormones on In Vitro Erythropoiesis

Abstract: A B S T R A C T The erythropoietic effect of various thyroid hormones has been studied using erythroid colony formation by canine marrow cells. Although erythropoietin was required for colony growth, physiologic levels ofthyroid hormones significantly enhanced colony numbers. The order of potency of the thyroid compounds in their in vitro erythropoietic effect parallels their known calorigenic potency in vivo, suggesting that the in vitro effect is physiologically relevant. A series ofstudies linked the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…A review of all these studies is far beyond the scope of this report. There are, however, a number of findings that seem to have particular relevance to the actions of T3 that we have described, and that consequently merit considera5The inhibitory effect of alprenolol on these responses to T3 is reminiscent ofthat reported by Popovic and co-workers (40), who demonstrated that T4 in vitro increases the erythroid colony-forming activity of canine marrow cells, and that this stimulation is inhibited by propranol. Apart from these two responses, we know of no other system in which an effect of thyroid hormones that occurs in the absence ofcatecholamines is blocked by an adrenergic antagonist.…”
Section: Effects Of Alprenololmentioning
confidence: 54%
“…A review of all these studies is far beyond the scope of this report. There are, however, a number of findings that seem to have particular relevance to the actions of T3 that we have described, and that consequently merit considera5The inhibitory effect of alprenolol on these responses to T3 is reminiscent ofthat reported by Popovic and co-workers (40), who demonstrated that T4 in vitro increases the erythroid colony-forming activity of canine marrow cells, and that this stimulation is inhibited by propranol. Apart from these two responses, we know of no other system in which an effect of thyroid hormones that occurs in the absence ofcatecholamines is blocked by an adrenergic antagonist.…”
Section: Effects Of Alprenololmentioning
confidence: 54%
“…Experiments employing trypsin-treated marrow cells suggest that erythroid progenitor cells have surface receptors for erythropoietin (2). These cells also have 8 Received for publication 14 May 1979 and in revised form 30 July 1979. tion and proliferation of erythroid precursor cells are enhanced by catecholamines (3) and other agents that interact with membrane-bound adenylate cyclase (4)(5)(6). It is unlikely, however, that activation of adenylate cyclase is the sole requirement for initiating erythroid cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones stimulate not only EPO production [2] but also the proliferation of erythroid progenitor cells [9,10]. Steroid hormones also stimulate erythropoiesis [3,.…”
Section: Discussionmentioning
confidence: 99%